Mast Cell Synapses and Exosomes: Membrane Contacts for Information Exchange - Carroll-Portillo, Amanda; Surviladze, Zurab; Cambi, Alessandra; Lidke, Diane S.; Wilson, Bridget S (Frontiers in Immunology, 2012)
In addition to their central role in allergy, mast cells are involved in a wide variety of cellular interactions during homeostasis and disease. In this review, we discuss the ability of mast cells to extend their mechanisms for intercellular communication beyond the release of soluble mediators. These include formation of mast cell synapses on antigen presenting surfaces, as well as cell-cell contacts with dendritic cells and T cells. Release of membrane-bound exosomes also provide for the transfer of antigen, mast cell proteins and RNA to other leukocytes. With the recognition of the extended role mast cells have during immune modulation, further investigation of the processes in which mast cells are involved is necessary. This reopens mast cell research to exciting possibilities, demonstrating it to be an immunological frontier.